1996
DOI: 10.1002/(sici)1096-9861(19960101)364:1<51::aid-cne5>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Central and primary visceral afferents to nucleus tractus solitarii may generate nitric oxide as a membrane-permeant neuronal messenger

Abstract: An anatomical basis was sought for the postulated roles of nitric oxide (NO) as a labile transcellular messenger in the dorsal vagal complex (NTS-X). The diaphorase activity of NO synthase was used as a marker of neurons in NTS-X that are presumed to convert L-arginine to L-citrulline and NO. Nicotinamide adenine dinucleotide phosphate diaphorase (NADPHd) staining patterns in the nucleus tractus solitarii (NTS) were spatially related to terminal sites of primary visceral afferents from 1) orosensory receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(26 citation statements)
references
References 95 publications
3
21
0
2
Order By: Relevance
“…The respiratory response to hypercapnia was similar in both groups of mice, suggesting that hypoxic chemosensory responses were selectively augmented in mutant mice deficient in nNOS. However, peripheral as well as central mechanisms dependent on nNOS integrity may contribute to the enhanced ventilatory responses to hypoxia observed in mutant mice (18,35). Our results suggest that NO produced by the nNOS isoform in the cat CB may inhibit the chemosensory responses to NaCN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The respiratory response to hypercapnia was similar in both groups of mice, suggesting that hypoxic chemosensory responses were selectively augmented in mutant mice deficient in nNOS. However, peripheral as well as central mechanisms dependent on nNOS integrity may contribute to the enhanced ventilatory responses to hypoxia observed in mutant mice (18,35). Our results suggest that NO produced by the nNOS isoform in the cat CB may inhibit the chemosensory responses to NaCN.…”
Section: Discussionmentioning
confidence: 99%
“…chemoreceptor; nitric oxide THE VENTILATORY EFFECTS of nitric oxide (NO) and the role played by nitric oxide synthase (NOS) isoforms are complex (14,18,30). In the nucleus tractus solitarii, NO plays a significant excitatory role in sustaining the ventilatory response to hypoxia (14,18,35). However, several lines of evidence indicate that NO produced within the carotid body (CB) is an inhibitory modulator of hypoxic chemoreception (2,8,20,25,34,38).…”
mentioning
confidence: 99%
“…A third possibility is that superoxide reacts with nitric oxide (NO) to produce peroxynitrite, which nitrates tyrosine residues in channel proteins, thereby increasing L-type Ca 2ϩ channel activity (Ohkuma et al, 2001). Indeed, there is evidence that NO synthase (NOS) is present in NTS (Ruggiero et al, 1996) and that inhibition of NOS produces alterations in baroreceptor function induced by AngII (Paton et al, 2001;Zucker et al, 2004). This conclusion was reached on the basis of studies using dominant-negative inhibitors of endothelial nitric oxide synthase (eNOS), which blocked the effects of AngII on baroreceptors in rat heart-brainstem preparations (Wong et al, 2002).…”
Section: Mechanisms Of Ros Actions On Ca 2؉ Currentsmentioning
confidence: 92%
“…We have previously shown that NMDA receptors within the nucleus tractus solitarii (NTS) are integral to the baroreceptor reflex (12), and others have suggested that nitroxidergic mechanisms may play a role in cardiovascular control through the NTS (13)(14)(15)(16)(17). We have sought to test this hypothesis and determine if NO• released from donor compounds elicits cardiovascular responses when administered into the NTS, the primary site of termination of vagal and glossopharyngeal cardiovascular afferent nerves.…”
Section: Wt Talmanmentioning
confidence: 99%
“…Direct evidence for the synthesis of S-nitrosothiols by the brain has also been provided by a recent report (34). The physiological relevance of nitroxidergic pathways in the NTS has been suggested by others who have shown that NOS is reduced in the NTS after removal of a nodose ganglion (14,17). Thus, vagal afferents, some of which contribute to cardiovascular reflex transmission, may have the capacity to synthesize NO•, and by implication, S-nitrosothiols.…”
Section: Wt Talmanmentioning
confidence: 99%